Western Balkans : Regional Economic Integration Issues Notes - World Bank Group (World Bank, Vienna, 2017)
The Western Balkan countries, Albania, Bosnia and Herzegovina, Kosovo, the former Yugoslav Republic (FYR) of Macedonia, Montenegro, and Serbia, achieved strong growth and poverty reduction since the start of the transition to market economies. Despite progress, today the six Western Balkan countries remain among the poorest in Europe, overtaken by the more successful neighboring countries in terms of convergence to EU standards of living. In summary, to converge faster to EU living standards, the Western Balkan countries need to continue to pursue a ‘three-pronged’ effort by implementing in parallel prudent macroeconomic policies, bold structural reforms, and measures to advance economic integration. Macroeconomic and fiscal stability, accompanied by decisive structural reforms are two necessary conditions to promote a sustainable and strong growth model, one that is based on private sector growth, investment, and higher exports. Structural reforms are key to unlocking the benefits of regional integration including productivity gains, investments, and job creation, all of which will support convergence to EU living standards. Indeed, economic integration is linked to productivity, as productivity is inherent in achieving economies of scale. And the speed and depth of reforms that rekindle income convergence will help advance the pace of economic integration.